Navigating barriers: two-year follow up on recommendations to improve the use of maternal health guidelines in Kosovo - Julia E. Moore; Sami Uka; Joshua P. Vogel; Caitlyn Timmings; Shusmita Rashid; A. Metin Gülmezoglu; Sharon E. Straus (BMC Public Health, 2016)
Abstract Background Although there are a growing number of initiatives aimed at supporting guideline implementation in resource-constrained settings, few studies assess progress on achieving next steps and goals after the initial activities are completed and the initial funding period has ended. The aim of the current study was to conduct a qualitative process evaluation of progress, barriers, facilitators, and proposed solutions to operationalize nine recommendations to prepare Kosovo to implement the 2012 World Health Organization (WHO) prevention and treatment of postpartum haemorrhage guideline. Methods/Design In 2012, we co-created nine recommendations designed to support implementing the WHO’s guideline on the prevention and treatment of postpartum haemorrhage in Kosovo. The current study uses a realist evaluation approach to assess activities and progress two years after the recommendations were developed. The study involved conducting qualitative focus groups and one-on-one interviews with participants from the first meeting to evaluate the activities and progress on the nine recommendations. Results Forty-three participants provided insights into the barriers and opportunities experienced to date and proposed future directions. Although progress has been made towards implementation of a number of the recommendations, scaling up has been limited by barriers, such as lack of awareness, limited resources, and evaluation challenges. Participants proposed addressing these barriers by building within- and between-country partnerships to facilitate guideline implementation. In addition, participants reported less progress on implementing recommendations related to broader cultural changes, which indicates a need for specific and actionable recommendations to operationalize implementation efforts. Conclusions In the two years since the initial meeting, there has been mixed progress on the recommendations. Based on participant feedback, we refined the recommendations so that they can be operationalized by health care system stakeholders in Kosovo to further support implementation efforts. It is beneficial to share these lessons learned throughout the implementation process to inform next steps in Kosovo and offer ideas for use in other settings.